HUBUNGAN PERSONAL HYGIENE DAN PENGGUNAAN APD DENGAN KEJADIAN DERMATITIS KONTAK PADA NELAYAN DI KELURAHAN PONTAP KOTA PALOPO - N, Suwandi; Amanah, Indra (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2022)
ABSTRACT Contact dermatitis is a skin disease, in the form of inflammation of the skin, generally can occur repeatedly due to the influence of exogenous factors and endogenous factors that can cause various clinical abnormalities, in the form of erythema, edema, papules, vesicles, scales and itching. Occupational diseases are diseases caused by work, work tools, materials, processes and the work environment. Thus, occupational disease is an artificial disease or man made disease. The purpose of this study was to determine whether there was a relationship between personal hygiene and the use of Personal Protective Equipment (PPE) on the incidence of contact dermatitis in fishermen in the Pontap sub-district, Palopo City. The sample in this study were 89 fishermen in the Pontap sub-district, Palopo City, which were determined by random sampling technique. The research design used was cross sectional with chi-square statistical test. The results of the study showed that respondents with positive contact dermatitis reached 28.1%, good personal hygiene reached 28.1% and bad was 71.9%. 14.6% with good use of personal protective equipment and still bad in reaching 85.4%. There is a significant relationship between personal hygiene and the incidence of contact dermatitis in fishermen in Pontap Village, Palopo City with p value = 0.009 and there is no relationship between the use of personal protective equipment and the incidence of contact dermatitis in fishermen in Pontap Village, Palopo City with p value = 0.663